2022
DOI: 10.3390/e24111540
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Seizure Detection Using Geometric Features Extracted from SODP Shape of EEG Signals and AsyLnCPSO-GA

Abstract: Epilepsy is a neurological disorder that is characterized by transient and unexpected electrical disturbance of the brain. Seizure detection by electroencephalogram (EEG) is associated with the primary interest of the evaluation and auxiliary diagnosis of epileptic patients. The aim of this study is to establish a hybrid model with improved particle swarm optimization (PSO) and a genetic algorithm (GA) to determine the optimal combination of features for epileptic seizure detection. First, the second-order dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…From past studies, hybrid algorithms are commonly used as improved algorithms, such as GA-PSO (Gupta et al, 2019 ; Liu et al, 2020 ), BAPSO (Almadhor et al, 2021 ), PSO-GWO (Dahmani and Yebdri, 2020 ), and hybrid multi-objective optimization algorithms: NSGA-MOPSO (Shuaipeng et al, 2017 ; Xie et al, 2022 ). Nevertheless, most hybrid algorithms directly combined the whole of two algorithms, without considering the complexity of the algorithm (Wang et al, 2022 ). Therefore, in this paper, superfluous operators are eliminated and only mutation is added to simplify the algorithm flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From past studies, hybrid algorithms are commonly used as improved algorithms, such as GA-PSO (Gupta et al, 2019 ; Liu et al, 2020 ), BAPSO (Almadhor et al, 2021 ), PSO-GWO (Dahmani and Yebdri, 2020 ), and hybrid multi-objective optimization algorithms: NSGA-MOPSO (Shuaipeng et al, 2017 ; Xie et al, 2022 ). Nevertheless, most hybrid algorithms directly combined the whole of two algorithms, without considering the complexity of the algorithm (Wang et al, 2022 ). Therefore, in this paper, superfluous operators are eliminated and only mutation is added to simplify the algorithm flow.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, substantia researches showed that network properties can capture the synergistic effect of abnormal paroxysmal firing of neurons more effectively than the characteristics of single channel signals (Wang et al, 2015b ; Busche and Hyman, 2020 ; Gao et al, 2021 ). In addition, the combination of multiple features can help to display EEG abnormalities from various angles and improve the recognition efficiency (Mahato and Paul, 2020 ; Pei et al, 2020 ; Narayan, 2021 ; Wang et al, 2022 ). For instance, Narayan ( 2021 ) extracted and combined the features of AAR parameters, Barlow parameters, Hjorth parameters, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations